2015
DOI: 10.1109/tsm.2014.2373353
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stress Effects on the Electrical Properties of p-Channel Polycrystalline-Silicon Thin-Film Transistors Fabricated via Metal-Induced Lateral Crystallization

Abstract: We developed a method to compact the glass sheets of a flat-panel displays that use metal-induced laterally crystallized (MILC) polycrystalline-silicon (poly-Si) thin-film transistors (TFTs), and the effects of thermal stress on the fabricated devices were compared against those of a bare-glass device. The glass substrate was exposed to a temperature of 650 • C for 40 h in order to suppress the glass shrinkage to 0.01 ppm, which suitable for a MILC poly-Si TFT process. The compressive strain that originates fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Thus, the MILC rate of LPCVD intrinsic Si was higher than that of PECVD intrinsic Si because reaction (6) is faster than reaction (9). It is well reportedly known that a-Si atomic bond breaking and migration at interface 1 is more difficult in PECVD a-Si than in LPCVD a-Si because of passivated Si-H bond in PECVD a-Si.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, the MILC rate of LPCVD intrinsic Si was higher than that of PECVD intrinsic Si because reaction (6) is faster than reaction (9). It is well reportedly known that a-Si atomic bond breaking and migration at interface 1 is more difficult in PECVD a-Si than in LPCVD a-Si because of passivated Si-H bond in PECVD a-Si.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…However, there are still some problems to be solved, such as high manufacturing cost and uniformity. To address these problems, the metal-induced lateral crystallization (MILC) technique has been developed [9][10][11][12][13][14][15][16]. The MILC technique has several advantages, such as low-batch cost, simple processing method, low-temperature (under 570 °C) process, and high electrical performance of the device [17,18,19,20].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Moreover, J. H. Park et. al also showed that fabricated a metal-induced lateral crystallized (MILC) poly-Si TFT in a bare glass which induces the shrinkage during MILC growth can observe a strain-effect in the device [8]; however the microcracks originating from the grain-boundaries are also generated and lead to a poor electrical and reliability performance..…”
Section: Introductionmentioning
confidence: 99%